Irreversible investment, uncertainty and hysteresis: A New Zealand Investigation - Goodson, Matthew (School of Management Working Papers, 1994)
This paper revolves on the idea that transitory shocks can leave behind permanent effects. The sunk cost nature of many capital expenditures means firms only commit themselves when they feel sufficiently certain about the future payoffe. Thus investment/abandonment requires certainty of a sustained up/down/um. In between these certainty poles, there exists a range of investment inaction which generates the possibility of hysteretic outcomes. Consider a large negative shock which creates high certainty of a down/um, causing firms to abandon. Later, when the shock disappears, the firm returns to inaction, leaving the economy with a permanently lower capitol stock. Section 1 shows that traditional investment models fail to incorporate uncertointy in a satisfactory manner. Section 2 outlines the recently developed theory of irreversible investment under uncertainty. The range of inaction is shown to be of significant size for plausible parameter values, it depends vitally on the degree of uncertainty, and only small sunk costs are needed for it to emerge. Section 3 uses Engle-Granger cointegration methodology to investigate uncertainty’s empirical role. A novel entropy related measure is constructed from business opinion data and is appended to an accelerator-type model. The coefficient on uncertainty is significantly negative and tentative signs of a structural break that were otherwise present are removed